Engaging the Emotions in Spanish Culture and History - Labanyi, Jo; Fernández, Pura; Delgado, Luisa Elena (Book collections on Project MUSE., 2016)
"Rather than being properties of the individual self, emotions are socially produced and deployed in specific cultural contexts, as this collection documents with unusual richness. All the essays show emotions to be a form of thought and knowledge, and a major component of social life--including in the nineteenth century, which attempted to relegate them to a feminine intimate sphere. The collection ranges across topics such as eighteenth-century sensibility, nineteenth-century concerns with the transmission of emotions, early twentieth-century cinematic affect, and the contemporary mobilization of political emotions including those regarding nonstate national identities. The complexities and effects of emotions are explored in a variety of forms--political rhetoric, literature, personal letters, medical writing, cinema, graphic art, soap opera, journalism, popular music, digital media--with attention paid to broader European and transatlantic implications"--